O Sistema Renina-Angiotensina na Doença de Alzheimer: revisão de literatura e estudo-piloto - Victor Teatini Ribeiro (2021)
Alzheimer’s Disease (AD), the leading cause of dementia worldwide, is the subject of growing scientific interest, given that part of its pathophysiology is yet to be unveiled. The renin-angiotensin system (RAS) is one of the most important physiological systems for homeostasis. As the knowledge about the RAS and its functions has accumulated, the system has been implicated in many pathological processes as well, including psychiatric and neurodegenerative diseases. However, the RAS role in AD pathophysiology, in particular, remains largely unexplored. This study addressed this gap in knowledge by targeting two main objectives: (1) to perform a comprehensive literature review about the RAS, AD and their possible intersection points; (2) to conduct a pilot-study to explore the RAS status in AD patients compared to cognitively healthy individuals, so as to generate hypotheses. To accomplish the first goal, we have non-systematically searched throughout PubMed/Medline and Google Scholar databases. We have found pre-clinical and clinical primary studies which directly addressed RAS participation in AD. As a result, we have written a narrative review article that summarizes all direct pieces of evidence and discusses at length the potential mechanisms behind them. In order to achieve the second objective, we have conducted a cross-sectional, case-control exploratory study which recruited 14 patients with AD and 14 cognitively healthy age-matched volunteers. Clinical data, neuropsychological test results, blood samples and magnetic resonance imaging (MRI) were obtained from all participants. We have measured plasma levels of angiotensin II (Ang II) and angiotensin-(1-7) [Ang-(1-7)], the effector peptides of RAS classical and alternative axis, respectively. Ang-(1-7) was found to be significantly reduced in AD patients. In the AD group, there was a positive correlation between circulating Ang-(1-7) and MRI markers of cerebrovascular lesions. Our findings strengthen the hypothesis that RAS alternative axis is downregulated in AD and points to a potential interaction mechanism. Moreover, these results provide a basis for conducting larger properly powered studies willing to test this hypothesis.